Increased Brain Neurotensin and NTSR2 Lead to Weak Nociception in NTSR3/Sortilin Knockout Mice - Devader, Christelle; Moreno, Sébastien; Roulot, Morgane; Deval, Emmanuel; Dix, Thomas; Morales, Carlos R.; Mazella, Jean (Frontiers in Neuroscience, 2016)
The neuropeptide neurotensin (NT) elicits numerous pharmacological effects through three different receptors (NTSR1, NTSR2 and NTSR3 also called sortilin). Pharmacological approaches and generation of NTSR1 and NTSR2-deficient mice allowed to determine the NT-induced antipsychotic like behaviour, the inhibitory of weak fear memory and the nociceptive signaling in a rat formalin tonic pain model to NTSR1. Conversely, the effects of NT on thermal and tonic nociceptions were mediated by NTSR2. However, the role of NTSR3/sortilin on the neurotensinergic system was not investigated. Here, by using C57Bl/6J mouse model in which the gene coding for NTSR3/sortilin has been inactivated, we observed a modification of the expression of both NTSR2 and NT itself. Quantitative PCR and protein expression using Western blot analyses and AlphaLisaTM technology resulted in the observation that brain NTSR2 as well as brain and blood NT were two fold increased in KO mice leading to a resistance of these mice to thermal and chemical pain. These data confirm that NTSR3/sortilin interacts with other NT receptors (ie ; NTSR2) and that its deletion modifies also the affinity of this receptor to NT.